鼠笼异步磁力联轴器隔离套的损耗计算及温度场分析 - 陈志鹏; 杨超君; 孔令营 (Jixie chuandong)
In order to obtain the loss calculation of the isolation units in squirrel-cage asynchronous magnetic coupling,the dynamic distribution of the spatial magnetic field is analyzed through equivalent surface current method and loss calculation of isolation units is obtained by Maxwell equation. On the basis of theoretical analysis,the temperature field is analyzed by using ANSYS,therefore the global temperature distribution and radial temperature distribution curves of squirrel-sage asynchronous magnetic coupling are obtained.The results show that maximum temperature of isolation units is 116.71℃and the minimum temperature is 114.69℃.The difference between max and min is small, the one inside has higher temperature and the outside is lower.The side of permanent magnet near the outer air gap has the maximum temperature 66.604℃,however,the other one has the minimum temperature 62.199℃.The temperature of the magnet is far away from dangerous temperature.So it ensures that the permanent magnet can work normally.The results have a guiding significant meaning for the temperature field analysis of the high power squirrel-cage asynchronous magnetic coupling.